IMPLEMENTASI PENDIDIKAN KARAKTER BERDASARKAN PERATURAN DAERAH KABUPATEN INDRAMAYU NOMOR 8 TAHUN 2015 DAN MAQASHID SYARIAH (Studi pada Siswa Kelas 4 Madrasah Ibtidaiyah Swasta Ma’had Al-Zaytun) - Nazwa Alaida Salsabila; Abdur Rahim; Muhammad Isa Asyofuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Schools hold a strategic role in implementing character education in accordance with applicable regulations. In Indramayu Regency, character education is regulated by Local Regulation Number 8 of 2015. Furthermore, character education values also align with the principles of Maqashid Syariah, particularly the aspect of intellect preservation (Hifdz Al-Aql). This research aims to examine the implementation of character education at Madrasah Ibtidaiyah Swasta Ma’had Al-Zaytun based on the Indramayu Local Regulation Number 8 of 2015 and the Maqashid Syariah principle (Hifdz Al-Aql). The research employed a descriptive qualitative method. Primary data were collected through interviews, observation, and documentation, while secondary data came from literature studies. Data analysis techniques included data reduction, data display, and conclusion drawing. The results indicate that the implementation of character education at this madrasah refers to the values listed in the Local Regulation Number 8 of 2015, such as discipline, responsibility, and maintaining cleanliness of both the classroom and the environment. Moreover, the Maqashid Syariah concept (Hifdz Al-Aql) is applied through a moral approach (such as direct teaching by teachers for students facing difficulties and providing advice) and a spiritual approach (such as the routine congregational Dhuhr prayer). Thus, the character education implemented in this madrasah is not only based on Regulation but is also rooted in Islamic Sharia principles that ensure the benefit of the intellect and the moral integrity of the students. Keywords: Character Education; Local Regulation; Maqashid Syariah; Hifdz Al-Aql; Islamic Elementary School.